Copper alloy powder for metal AM and manufacturing method for additive manufacturing

JP7622901B2Active Publication Date: 2025-01-28MITSUBISHI MATERIALS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024506148
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-24
Filing Date
2023-10-24
Publication Date
2025-01-28
Estimated Expiration
2043-10-24

AI Technical Summary

Benefits of technology

【0028】 本発明によれば、金属AMにより作製した造形体の微細構造の再現性が高く、ボイド等の構造欠陥が少ない高品質な積層造形物を安定して製造可能な金属AM用銅合金粉末、および、積層造形物の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622901000003
    Figure 0007622901000003
  • Figure 0007622901000004
    Figure 0007622901000004
  • Figure 0007622901000005
    Figure 0007622901000005
Patent Text Reader

Abstract

This copper alloy powder for metal AM is composed of a copper alloy containing Cr, and a Cr compound layer having a Cr-containing compound is formed on the surface of the copper alloy particles constituting the copper alloy powder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to copper alloy powder for metal additive manufacturing (metal AM), which is optimal for metal AM technology, and a manufacturing method for additively manufactured objects. This application claims priority based on Japanese Patent Application No. 2022-169924, filed on October 24, 2022, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, metal AM technology, which mainly uses powder as the raw material to create products using a metal 3D printer, has been put to practical use as a method for manufacturing metal parts with various three-dimensional shapes. The main metal AM technologies that use metal powder include powder bed fusion (PBF) using electron beams or laser light, and the binder jet method. Copper alloys have many basic properties suitable for industrial applications, such as electrical conductivity, thermal conductivity, mechanical properties, wear resistance, and heat resistance, and are used as materials for various components. In recent years, attempts have been made to form components of various shapes by metal AM using copper alloy powder in various fields such as space and electrical component applications, and there is a growing need for copper and copper alloy parts manufactured by metal AM.

[0003] For example, Patent Document 1 proposes a technique for producing an additive manufacturing object by metal AM using a copper alloy powder containing either Cr or Si. Moreover, Patent Document 2 proposes a technique for producing an additive manufacturing object by metal AM using a copper alloy powder containing Cr and Zr. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-211062 A [Patent Document 2] JP 2019-070169 A [Non-patent literature]

[0005] [Non-Patent Document 1] YM Arisoy et. al., "Influence of scan strategy and process parameters on microstructure and its optimization in additively manufactured nickel alloy 625 via laser powder bed fusion", The International Journal of Advanced Manufacturing Technology, Volume 90, pp 1393-1417 (2017). Summary of the Invention [Problem to be solved by the invention]

[0006] Metal structures created by metal AM are used as structural components for a variety of applications, so if voids are present in the additively manufactured body or if the microstructure of the metal material is uneven, this can cause problems in terms of thermomechanical and electrical reliability. Currently, the most commonly used building method for metal AM is laser PBF, and attempts have also been made to use laser PBF for copper and copper alloys. Incidentally, when performing additive manufacturing using a method of irradiating a laser beam or an electron beam, a thin layer of powder is first formed (powder bed), and then this powder bed is locally irradiated with a laser or an electron beam to melt and solidify the material. However, in the case of copper and copper alloys, compared to other metal materials such as iron, titanium, and nickel, copper itself has a high reflectance in the visible and infrared ranges, which causes the melting behavior of the copper alloy powder to become unstable during the laser PBF process, and voids are likely to occur inside the additively manufactured object, resulting in a number of issues such as unstable quality of the object manufactured by laser PBF and poor productivity, and there is a demand for improvements in the productivity and quality of copper and copper alloys manufactured by laser PBF.

[0007] Currently, the most widely used form of raw material for metal AM is powder. For example, in metal AM using laser PBF, the electromagnetic wave absorption characteristics of the particles due to the coupling and interaction between the surface layer of the particles constituting the raw material powder and the electromagnetic wave affect the melting behavior of the raw material powder, and greatly affect the productivity of the parts and the quality including the defect density of the parts. For example, in a metal AM process using a powder bed, the thickness of the powder bed formed in one lamination process is, for example, about several tens of μm (Non-Patent Document 1), and the raw material powder is melted by irradiating such a relatively thin powder bed with converged electromagnetic waves, and the desired molded structure is realized by repeating numerous laminations and melting and solidification. The electromagnetic wave absorption characteristics of solids have a significant effect on the elementary process of such additive manufacturing using a powder bed. For example, since the electromagnetic wave absorption characteristics of solids are affected by the material composition, it is extremely important to increase the uniformity of the material composition and microstructure of the powder in order to achieve stable quality and high productivity in the entire additive manufacturing product.

[0008] Here, the electromagnetic wave absorption characteristics of copper and copper alloys can be improved, for example, by simply adding a substance with a high absorption rate of the target laser wavelength as a component other than copper. However, as many past metallurgical studies have shown, when copper and copper alloys are used for a certain application, the properties required for that application can only be realized by appropriately selecting the type and amount of elements added to copper. Therefore, in order to improve the productivity and quality of metal AM objects made of copper or copper alloys, in other words, to improve the laser absorption of raw powders of copper or copper alloys, a simple approach such as adding various foreign elements with high laser absorption rates to copper or copper alloys of optimized composition or increasing the amount of such elements may deteriorate the performance of copper alloys required for various applications. Therefore, it has been required to realize copper alloy powders for metal AM with improved laser absorption characteristics while maintaining a material composition that can fully ensure the performance of copper alloys required for various applications.

[0009] One important approach to improve the laser absorption properties of powders is to improve the laser absorption ability of each particle by surface modification of the particle surface that constitutes the powder. For this surface modification, it is possible to apply a coating of a substance that has a high absorption rate at the laser wavelength used in metal AM to the surface of each particle of the powder having the desired copper alloy composition. As an approach to coating the particle surface, a desired coating material can be formed on the particle surface using a wet or gas phase process. However, such a coating process is accompanied by problems such as the control of the thickness of the coating layer on each particle, as well as the reproducibility of the coating thickness and the homogeneity of the coating material throughout the powder, resulting in a number of issues in the productivity and quality of the molded object.

[0010] In addition, as a result of various past research and development efforts, copper alloy materials that achieve high mechanical strength while maintaining high electrical conductivity, as well as materials with excellent heat resistance, have already been developed, and in metal AM, there is a societal demand to use such existing high-performance copper alloy materials to create metal AM parts with desired shapes. However, controlling the amount of components in the material formed by coating while also controlling the material composition of the copper alloy of the final product not only places a significant burden on the manufacturing process, but there were concerns that it would result in a number of major problems, such as deterioration of the performance of the molded parts due to variations in composition and microstructure, deterioration of mass producibility of parts, and issues with maintaining the quality of the parts.

[0011] Furthermore, one of the factors that can cause structural defects in metal AM objects is the generation of voids due to the entrapment of gas, etc. When conventional copper alloy powder is used for additive manufacturing by the PBF method, gas is generated due to impurities contained in the copper alloy powder when the powder is melted, and the molten copper alloy or solidified copper alloy traps the gas components, which can cause voids to form inside the additive manufactured object, making it difficult to stably produce high-quality additive manufactured objects.

[0012] Furthermore, when additive manufacturing is performed by irradiating a powder bed of the raw material with laser light or an electron beam, if there is a lack of reproducibility of the microstructure of the raw material powder, including the reproducibility of the composition of the powder particles at each location irradiated with the laser light, the melting behavior of the powder will be non-uniform, which could result in the occurrence of structural defects such as voids inside the molded object or a deterioration of the mechanical properties due to non-uniformity in the metal composition of the molded object.

[0013] In addition, the reproducibility of the microstructure of the raw material powder, including the reproducibility of the powder's material composition, is a similar problem to other metal AM methods such as the binder jet method. In metal AM of copper alloys, improving productivity has been a major challenge due to the issues with the various raw materials.

[0014] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide a copper alloy powder for metal AM that can stably produce high-quality additively molded objects with high reproducibility of the microstructure of objects created by metal AM and few structural defects such as voids, and a method for manufacturing additively molded objects. [Means for solving the problem]

[0015] From the above viewpoint, the present inventors have conducted research and development to produce copper alloy powder that has the copper alloy composition required for practical applications and can be used to produce high-performance, high-quality copper alloy parts with high productivity using a metal AM process. As a result, when a high-purity copper alloy is used as a raw material and a powdering process is performed, it has been found that, while the copper alloy powder as a whole has few impurities and maintains a uniform composition, when focusing on the individual particle surfaces in the copper alloy powder, a thin layer is formed on the copper alloy particle surface to be irradiated with a laser. Furthermore, it has been found that, in the thin layer formed on the copper alloy particle surface, a characteristic structure in which powder constituent elements that exhibit higher laser absorption than copper are frequently present compared to the inside of the bulk copper alloy particle, is spontaneously generated in a direct powdering process from the copper alloy raw material without going through an individual coating process or an additional process on the powder.

[0016] In addition to these structural features of the copper alloy particle surface, the copper alloy powder is derived from high-purity copper alloy raw materials, which means that it contains fewer impurities that lead to gas components, thereby suppressing gas generation during melting.This makes it possible to realize dense copper alloy bodies that have high thermal, electrical, and mechanical properties, and it has been discovered that it is possible to manufacture copper alloy powder for metal AM that can achieve high productivity and high quality of copper alloy bodies that exhibit such high performance.

[0017] Specifically, in copper alloy powder produced from a copper alloy ingot that contains Cr while having a uniform composition with sufficiently reduced impurities, it is possible for Cr-containing precipitates to form on the surface of each particle constituting the copper alloy powder at the copper crystal grain boundaries and on the copper crystal grains (on the surfaces of the copper crystal grains).It was discovered that when additive manufacturing is performed using copper alloy powder for metal AM having such a surface microstructure, it is possible to produce a dense copper alloy object in which the occurrence of structural defects such as voids is suppressed.

[0018] The present invention has been made based on the above-mentioned findings, and a copper alloy powder for metal AM according to a first aspect of the present invention is a copper alloy powder for metal AM used in metal AM, The copper alloy contains 0.1% by mass or more and 1.5% by mass or less of Cr as an alloying element, and when one or more selected from Zr, Si, and Ni are contained as alloying elements other than Cr, the Zr content is 0.2% by mass or less, the Si content is 0.8% by mass or less, and the Ni content is 3.0% by mass or less,The copper alloy powder is characterized in that the total amount of additive elements and impurity elements (excluding O, H, S, and N) other than the alloy elements is 0.07 mass% or less, and a Cr compound layer having a Cr-containing compound is formed on the surface of the copper alloy particles constituting the copper alloy powder.

[0019] The copper alloy powder for metal AM of embodiment 1 of the present invention is made of a copper alloy containing Cr, and a Cr compound layer containing a Cr-containing compound is formed at the copper grain boundaries and on the copper grains (the surfaces of the copper grains) on the particle surfaces that make up the copper alloy powder. This means that laser absorption is efficient on the particle surfaces that make up the copper alloy powder, and the microstructure of the shaped body produced by metal AM is highly reproducible, making it possible to consistently produce high-quality additively shaped objects with few structural defects such as voids.

[0020] In a second aspect of the present invention, in the copper alloy powder for metal AM of the first aspect, the Cr compound layer preferably contains oxygen. According to the copper alloy powder for metal AM of aspect 2 of the present invention, the Cr compound layer formed on the particle surfaces constituting the copper alloy powder contains oxygen, which means that laser absorption is more efficient on the particle surfaces constituting the copper alloy powder, making it possible to consistently produce high-quality additively manufactured objects with high reproducibility of the microstructure of objects produced by metal AM and with few structural defects such as voids.

[0021] In a third aspect of the present invention, in the copper alloy powder for metal AM of the first or second aspect, it is preferable that, upon cross-sectional observation of the copper alloy particles constituting the copper alloy powder, Cr-containing compounds are distributed at crystal grain boundaries throughout the copper alloy particles. According to the copper alloy powder for metal AM of aspect 3 of the present invention, Cr-containing compounds are distributed at the crystal grain boundaries of all of the copper alloy particles constituting the copper alloy powder, making it possible to produce additive manufacturing objects with excellent electrical conductivity, thermal conductivity, and strength.

[0022] In a fourth aspect of the present invention, in the copper alloy powder for metal AM according to any one of the first to third aspects, it is preferable that the 50% cumulative particle diameter D50 on a volume basis measured by a laser diffraction / scattering method is in the range of 5 μm or more and 120 μm or less. According to the copper alloy powder for metal AM of aspect 4 of the present invention, the volume-based 50% cumulative particle diameter D50 measured by a laser diffraction / scattering method is in the range of 5 μm or more and 120 μm or less, so that it has a particle size distribution suitable for metal AM and enables the stable production of additive manufacturing objects.

[0023] In a fifth aspect of the present invention, in the copper alloy powder for metal AM according to any one of the first to fourth aspects, it is preferable that the volume-based 10% cumulative particle diameter D10 measured by a laser diffraction / scattering method is in the range of 1 μm or more and 80 μm or less. According to the copper alloy powder for metal AM of aspect 5 of the present invention, the volume-based 10% cumulative particle diameter D10 measured by a laser diffraction / scattering method is in the range of 1 μm or more and 80 μm or less, so that it has a particle size distribution suitable for metal AM and enables the stable production of additive manufacturing objects.

[0024] In a sixth aspect of the present invention, in the copper alloy powder for metal AM according to any one of the first to fifth aspects, it is preferable that the volume-based 90% cumulative particle diameter D90 measured by a laser diffraction / scattering method is in the range of 10 μm or more and 150 μm or less. According to the copper alloy powder for metal AM of aspect 6 of the present invention, the volume-based 90% cumulative particle diameter D90 measured by a laser diffraction / scattering method is in the range of 10 μm or more and 150 μm or less, so that it has a particle size distribution suitable for metal AM and enables the stable production of additive manufacturing objects.

[0025] The manufacturing method of an additively molded object of aspect 7 of the present invention preferably comprises a preparation step of preparing a copper alloy powder for metal AM of any one of aspects 1 to 6, a first step of forming a powder bed containing the copper alloy powder for metal AM, and a second step of solidifying the copper alloy powder for metal AM at a predetermined position in the powder bed to form a molding bed, thereby producing an additively molded object by sequentially repeating these steps.

[0026] According to the manufacturing method for an additive manufacturing object of aspect 7 of the present invention, since the copper alloy powder for metal AM of any one of aspects 1 to 6 is used, it is possible to stably manufacture high-quality additive manufacturing objects with high reproducibility of the microstructure of the object produced by metal AM and with few structural defects such as voids.

[0027] According to an eighth aspect of the present invention, in the method for manufacturing an additive manufacturing object according to the seventh aspect, it is preferable to further include a heat treatment step of performing a heat treatment in a temperature range of 300° C. or higher and lower than the melting point of pure copper after the manufacturing step. By carrying out an appropriate heat treatment according to the application of the produced additive manufacturing product, it is possible to control the microstructure of the molded copper alloy, and it is possible to realize the desired mechanical properties and conductive properties. By carrying out heat treatment within the temperature range of the manufacturing method of the eighth aspect of the present invention, a copper alloy molded product with an appropriately controlled microstructure is realized. Effect of the Invention

[0028] According to the present invention, it is possible to provide a copper alloy powder for metal AM that can stably produce high-quality additively molded objects with high reproducibility of the microstructure of objects produced by metal AM and few structural defects such as voids, and a method for manufacturing additively molded objects. [Brief description of the drawings]

[0029] [Figure 1] FIG. 1 is a schematic explanatory diagram of a copper alloy powder for metal AM according to the present embodiment. [Figure 2A]This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment after etching for 15 minutes from the outermost surface of the particle (C18000), and is a secondary electron image. [Figure 2B] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment after etching for 15 minutes from the outermost surface of the particle (C18000), and is a Cr mapping image. [Figure 2C] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment after etching for 15 minutes from the outermost surface of the particle (C18000), and is a Si mapping image. [Figure 2D] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment after etching for 15 minutes from the outermost surface of the particle (C18000), and is a Ni mapping image. [Figure 2E] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment, after etching for 15 minutes from the outermost surface of the particle (C18000), and is a composite element mapping image. [Figure 3A] FIG. 18 shows the results of Auger electron spectroscopy analysis of the surface of a particle constituting the copper alloy powder for metal AM of this embodiment (C18150), and is a secondary electron image of the particle surface after 15 minutes of etching from the outermost surface. [Figure 3B] FIG. 18 shows the results of Auger electron spectroscopy analysis of the surfaces of particles constituting the copper alloy powder for metal AM of this embodiment (C18150), and is a composite image of elemental mapping of the particle surfaces. [Figure 3C] FIG. 18 shows the results of Auger electron spectroscopy analysis of the surfaces of particles constituting the copper alloy powder for metal AM of this embodiment (C18150), and is the result of semi-quantitative analysis of the particle surfaces after etching for 30 minutes from the outermost surface. [Figure 4A] 1 is an example of an intensity depth profile by Auger electron spectroscopy analysis of the particle surface of a copper alloy powder (C18000) for metal AM according to this embodiment. [Figure 4B]1 is an example of an intensity depth profile by Auger electron spectroscopy analysis of the particle surface of a copper alloy powder (C18150) for metal AM according to this embodiment. [Figure 5A] 1 shows the results of Auger electron spectroscopy analysis of a particle cross-section of the copper alloy powder (C18000) for metal AM according to the present embodiment, and is a secondary electron image. [Figure 5B] 1 is a result of Auger electron spectroscopy analysis of a particle cross section of the copper alloy powder (C18000) for metal AM according to the present embodiment, and is an element mapping image of Cr. [Figure 6A] 1 is a secondary electron image showing the results of a scanning electron microscope analysis of a particle cross section of the copper alloy powder for metal AM (C18150) according to the present embodiment. [Figure 6B] 1 is a scanning electron microscope analysis result of a particle cross section of the copper alloy powder for metal AM (C18150) according to the present embodiment, and is an element mapping image of Cr. [Figure 6C] 1 is a scanning electron microscope analysis result of a particle cross section of a copper alloy powder for metal AM (C18150) according to the present embodiment, and is an element mapping image of Zr. [Figure 7] FIG. 1 is a flow diagram of a method for producing a copper alloy powder for metal AM according to the present embodiment. [Figure 8] FIG. 1 is a schematic explanatory diagram of a continuous casting device used when producing the copper alloy powder for metal AM according to the present embodiment. [Figure 9] FIG. 2 is a flow diagram of a method for manufacturing a layered object according to the present embodiment. [Figure 10] FIG. 2 is a schematic explanatory diagram of another continuous casting device used when producing the copper alloy powder for metal AM according to the present embodiment. [Figure 11] FIG. 1 shows an example of an analysis result of the particle surface of the copper alloy powder for metal AM according to the present embodiment, using high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM), in which (A) shows a HAADF image, (B) shows Cu mapping, (C) shows Si mapping, and (D) shows Cr mapping. [Figure 12] These are the results of electron diffraction analysis using a transmission electron microscope of the particle surface of the copper alloy powder for metal AM of this embodiment, in which (A) is a bright-field image, (B) is the electron diffraction pattern of the Cu portion (Cu[1-10]), and (C) is the electron diffraction pattern of the CrSi-based compound derived from the CrSi-based precipitates (Cr3Si[01-2]). [Figure 13] Examples of analysis results of grain boundary precipitates of copper alloy particles in the copper alloy powder for metal AM according to this embodiment, using high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM). (A) HAADF image, (B) Cr mapping, (C) Zr mapping. In (A), the arrows indicate Cr-based precipitates and Zr-based precipitates. [Figure 14] FIG. 1 shows an example of the results of a transmission electron microscope analysis of precipitates at grain boundaries in the copper alloy powder for metal AM according to the present embodiment, in which (A) is a bright field image, and (B) is a fast Fourier transform pattern (the analysis results of the area enclosed in the square frame in (A). Cr2Zr(Hexagonal)[-21-4]). [Figure 15] FIG. 1 shows an example of the results of a transmission electron microscope analysis of precipitates at grain boundaries in the copper alloy powder for metal AM according to the present embodiment, in which (A) is a bright-field image, and (B) is a fast Fourier transform pattern (analysis results of the area enclosed in the square frame in (A); Cu8Zr3(Orthorhombic)[21-4]). [Figure 16A] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment (C18000), and is a secondary electron image of the outermost particle surface before etching. [Figure 16B] This is an Auger electron spectroscopy analysis of the particle surface of the copper alloy particles constituting the copper alloy powder for metal AM of the present embodiment (C18000), and is a Cr mapping image of the outermost particle surface before etching. The arrows indicate the presence of Cr-based precipitates on the copper crystal particles. [Figure 16C]This is an analysis result of the particle surface of the copper alloy particle constituting the copper alloy powder for metal AM of the present embodiment by Auger electron spectroscopy (C18000), and is a Cr mapping image of the particle surface after etching for 5 minutes from the outermost surface of the particle shown in Figure 16A. The arrow indicates the presence of Cr-based precipitates on the copper crystal particles. [Figure 16D] This is an Auger electron spectroscopy analysis result (C18000) of the particle surface of the copper alloy particle constituting the copper alloy powder for metal AM of this embodiment, and is a Cr mapping image of the particle surface after etching for 15 minutes from the outermost surface of the particle shown in Figure 16A. The arrow indicates the presence of Cr-based precipitates on the copper crystal particles. [Figure 16E] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment (C18000), and is a Cr mapping image of the particle surface after etching for 30 minutes from the outermost surface of the particle shown in Figure 16A. [Figure 16F] This is the result of an Auger electron spectroscopy analysis of the particle surface of a copper alloy particle constituting the copper alloy powder for metal AM of this embodiment (C18000), and is a Cr mapping image of the particle surface after etching for 50 minutes from the outermost surface of the particle shown in Figure 16A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, a copper alloy powder for metal AM according to one embodiment of the present invention will be described with reference to the attached drawings. The copper alloy powder for metal AM of this embodiment is a copper alloy powder used for metal AM. Note that the copper alloy powder for metal AM of this embodiment is particularly suitable for the PBF method using a laser.

[0031] In the copper alloy particle 50 of the copper alloy powder for metal AM according to this embodiment, as shown in FIG. 1, a Cr compound layer 52 having a Cr-containing compound is formed on the particle surface. That is, in the copper alloy particle 50 of the copper alloy powder for metal AM of this embodiment, as shown in FIG. 1, it is preferable that the particle body 31 is made of a copper alloy containing Cr, and a Cr compound layer 52 is formed on the outer peripheral surface (or surface layer) of this particle body 51. In this embodiment, the surface (particle surface) (or surface layer) of the copper alloy particle of the copper alloy powder for metal AM refers to a region from the outermost surface of the particle to a depth of 100 nm. In the copper alloy particle 50 of the copper alloy powder for metal AM according to this embodiment, the Cr compound layer 52 preferably contains oxygen, as shown in FIGS. 4A and 4B.

[0032] In addition, the thickness of the Cr compound layer 52 on the particle surface of the copper alloy powder for metal AM is preferably 1 nm or more and 100 nm or less. More specifically, the thickness of the Cr compound layer 52 is preferably 1 nm or more, and may be 5 nm or more, 10 nm or more, 20 nm or more, 30 nm or more, or 50 nm or more. Also, the thickness of the Cr compound layer 52 is preferably 100 nm or less, and may be 95 nm or less, 90 nm or less, 80 nm or less, or 70 nm or less.

[0033] The Cr compound layer 52 is preferably a layer disposed on the outer peripheral surface (or surface layer) of the particle body 51, and contains a Cr compound including precipitates containing Cr. In the Cr compound layer 52, the Cr compound may be contained in the Cr compound layer 52 as dot-shaped precipitates uniformly or non-uniformly dispersed. In the Cr compound layer 52, the Cr compound may be contained in the Cr compound layer 52 as a plurality of amorphous island-shaped precipitates (amorphous aggregates) uniformly or non-uniformly dispersed. The Cr compound may be precipitated along the copper crystal grain boundaries on the surface of the particle body 51 .

[0034] In the Cr compound layer 52, the Cr compound may be precipitated so as to continuously cover the outer peripheral surface (or surface layer) of the particle body 51. In this case, the entire outer peripheral surface of the particle body 51 may be covered with the Cr compound, or a part of the outer peripheral surface (or surface layer) (e.g., 50% or more of the outer peripheral surface) may be continuously covered. Note that a part of the outer peripheral surface (or surface layer) of the particle body 51 (e.g., 50% or more of the outer peripheral surface) may be discontinuously (or in an island shape) covered.

[0035] The thickness of the Cr compound layer 52 can be calculated from the time until the particle surface made of SiO2 is etched by ion etching at an etching rate of 1.08 nm / min, the surface of the copper alloy particle 50 of the copper alloy powder for metal AM is etched under these standard etching conditions, the surface of the copper alloy particle 50 of the copper alloy powder for metal AM is analyzed by Auger electron spectroscopy using a scanning Auger electron spectrometer PHI700xi manufactured by ULVAC-PHI, Inc., a Cr mapping image showing the Cr compounds is obtained, and a chromium (Cr) intensity depth profile (graph showing the relationship between intensity and etching time shown in Figure 4A or Figure 4B) is obtained, and the chromium (Cr) intensity (cps) stops decreasing or becomes equal to or below a predetermined value. That is, it can be calculated as follows: time (min) until the chromium (Cr) intensity (cps) stops decreasing or becomes equal to or below a predetermined value × etching rate under standard conditions 1.08 nm / min = thickness of the Cr compound layer 52.

[0036] Furthermore, in this embodiment, it is preferable that the Cr-containing compound is distributed at the crystal grain boundaries of the entire copper alloy particle in cross-sectional observation of the copper alloy particle 50 constituting the copper alloy powder. Here, the entire copper alloy particle refers to the surface and the inside of the particle in one copper alloy particle.

[0037] 2A to 2E, a particle body 51 of a copper alloy particle 50 of the copper alloy powder for metal AM according to this embodiment is polycrystalline, and it is confirmed that a Cr-containing compound consisting of a compound containing Cr is distributed on the surface of the particle body 51. The Cr-containing compound is distributed both at the grain boundaries and within the grains. In this embodiment, the diameter or major axis along the particle surface of the Cr-containing compound derived from the Cr-based precipitates present in the Cr compound layer 52 is preferably within a range of 1 nm to 1000 nm. The diameter or major axis along the particle surface of the Cr-containing compound may be 800 nm or less, 500 nm or less, 300 nm or less, 100 nm or less, or 80 nm or less. The lower limit of the diameter or major axis along the particle surface of the Cr-containing compound may be 5 nm or more, or 10 nm or more, and the upper limit may be 90 nm or less, or 80 nm or less.

[0038] Here, the diameter or long axis of the Cr-containing compound along the particle surface is the diameter or long axis of each aggregate of precipitates of the Cr-containing compound along the outer surface of the particle body 51 when the Cr-containing compound is dispersed in dot shapes or irregular island shapes (island shapes) on the outer surface of the particle body 51, and can be measured from an image of the outer surface of the particle body 51 analyzed by Auger electron spectroscopy using a scanning Auger electron spectroscopy analyzer PHI700xi manufactured by ULVAC-PHI, Inc.

[0039] When precipitates derived from Cr-containing compounds are dispersed on the surface of the particle body 51 of the copper alloy particle 50 of the copper alloy powder for metal AM of this embodiment, the density of the precipitates derived from the Cr-containing compounds in the Cr compound layer 52 is preferably such that at any point on the outermost surface of the Cr compound layer 52, an area ratio of the precipitates derived from the Cr-containing compounds is 15% or more, and preferably, an area ratio of the precipitates derived from the Cr-containing compounds is 20% or more.

[0040] The density of the precipitates derived from the Cr-containing compounds in the Cr compound layer 52 was measured by analyzing the outermost surface of the Cr compound layer 52 by Auger electron spectroscopy using a scanning Auger electron spectrometer PHI700xi manufactured by ULVAC-PHI, Inc., and measuring the density of the precipitates in the Cr compound layer 52 at a density of 1 μm. 2 The area occupancy rate of Cr-containing compounds (Cr-based precipitates) can be calculated from the size and number of precipitates of Cr-containing compounds per unit area.

[0041] When the precipitates derived from the Cr-containing compound in the Cr compound layer 52 are precipitated along the copper grain boundaries on the surface of the particle body 51, and when the surface of the particle body 51 is observed using Auger electron spectroscopy, the copper grain boundaries can be seen as lines. In this case, the density (linear density) of the precipitates derived from the Cr-containing compound per unit length of the copper grain boundaries can be obtained. The outermost surface of the Cr compound layer 52 may be analyzed by Auger electron spectroscopy using a scanning Auger electron spectrometer PHI700xi manufactured by ULVAC-PHI, Inc., and the copper crystal grain boundaries of the image may be observed to determine the linear density per 1 μm of grain boundary length from the proportion of precipitates derived from Cr-containing compounds per 1 μm of grain boundary length. In this case, it is preferable to observe a portion where the linear density is 30% or more.

[0042] Furthermore, as shown in Figures 5A and 5B and 6A to 6C, in the copper alloy particle 50 of the copper alloy powder for metal AM of this embodiment, analysis of the cross section of the particle revealed that Cr-containing compounds consisting of compounds containing Cr are distributed at the crystal grain boundaries inside the particle body 51. In this embodiment, it is preferable that the diameter or major axis of the Cr-containing compound observed at the grain boundary of the particle body 51 is within the range of 1 nm or more and 1000 nm or less as a result of cross-sectional observation.

[0043] The copper alloy constituting the copper alloy particles 50 of the copper alloy powder for metal AM of this embodiment preferably contains Cr as an alloying element in the range of 0.01 mass % or more and 10 mass % or less. The lower limit of the Cr content is more preferably 0.1 mass% or more, and even more preferably 0.5 mass% or more.The upper limit of the Cr content is more preferably 3 mass% or less, and even more preferably 1.5 mass% or less. Furthermore, in this embodiment, the copper alloy constituting the copper alloy particle 50 of the copper alloy powder for metal AM may contain alloy elements other than Cr. For example, the copper alloy may contain Si and Ni as alloy elements other than Cr. In this case, as shown in Figures 2A to 2E, it is preferable that the Cr-containing compound is distributed on the surface of the particle body 51. Also, as shown in Figures 5A and 5B, it is preferable that the Cr-containing compound is distributed on the grain boundary in the cross-sectional observation of the particle. Copper alloys containing Cr, Si, and Ni include those containing Cr in the range of 0.1% by mass to 0.8% by mass, Si in the range of 0.4% by mass to 0.8% by mass, Ni in the range of 1.8% by mass to 3.0% by mass, with the remainder being copper and impurities (a composition equivalent to so-called C18000). In addition, in the composition of the copper alloy constituting the copper alloy particles 50 of the copper alloy powder for metal AM, the numerical accuracy error is ±10% (excluding O, H, S, and N).

[0044] In the copper alloy containing Cr, Si, and Ni, it is preferable that CrSi-based compounds and NiSi-based compounds are contained. Among them, the CrSi-based compounds, which are Cr-containing compounds, specifically include Cr3Si, etc., and the NiSi-based compounds specifically include Ni5Si2, etc. The copper alloy containing Cr, Si, and Ni may contain, in addition to the CrSi-based compound and NiSi-based compound, a copper alloy containing Cr, Si, and Ni and an oxide of the copper alloy. The oxide may be formed when the copper alloy powder for metal AM of the present embodiment is exposed to an oxygen-containing atmosphere or a moisture-containing atmosphere.

[0045] Also, for example, the copper alloy may contain Zr as an alloy element other than Cr. Such a copper alloy preferably contains Zr in the range of 0.01 mass% to 10 mass%. In this case, as shown in Figures 3A to 3C, it is preferable that the Zr-containing compound is distributed on the surface of the particle body 51. Also, as shown in Figures 6A to 6C, it is preferable that the Zr-containing compound is distributed on the grain boundary in the cross-sectional observation of the particle. In addition, examples of copper alloys containing Cr and Zr include those having a composition in which Cr is in the range of 0.5 mass% or more and 1.5 mass% or less, Zr is in the range of 0.02 mass% or more and 0.2 mass% or less, and the balance is copper and impurities (a composition equivalent to so-called C18150).

[0046] A specific example of a Cr-containing compound contained in a copper alloy containing Cr and Zr is Cr2Zr. In the Cr compound layer 52, Cr may exist as a simple substance. The Cr compound layer 52 may also contain an oxide of the element that constitutes the particle body 51 . Furthermore, the copper alloy containing Cr and Zr may contain a Zr-containing compound, and a specific example of the Zr-containing compound is Cu8Zr3.

[0047] In this embodiment, the alloying elements are Cr, Si, Ni, and Zr. The copper alloy constituting the copper alloy particles 50 of the copper alloy powder for metal AM contains one or two of Cr, Si, Ni, and Zr as alloying elements. In this embodiment, the impurities are components containing the impurity elements described below as well as O, H, S, and N.

[0048] Furthermore, the copper alloy constituting the copper alloy particles 50 of the copper alloy powder for metal AM may contain additive elements and impurity elements (excluding O, H, S, and N) other than the alloy elements. In this embodiment, the additive elements are elements that are intentionally added to the copper alloy powder for metal AM of this embodiment. On the other hand, the impurity elements (excluding O, H, S, and N) are elements that are unintentionally mixed into the copper alloy powder for metal AM of this embodiment, and originate from contamination during the manufacturing process or impurities contained in trace amounts in the raw materials. The impurity elements may be unavoidable impurities. Examples of additive elements and impurity elements (excluding O, H, S, and N) other than the alloy elements constituting the copper alloy particles 50 of the copper alloy powder for metal AM include Mg, Ti, Al, Zn, Ca, Sn, Pb, Fe, Mn, Te, Nb, P, Co, Sb, Bi, Ag, Ta, W, and Mo. The additive elements and impurity elements other than the alloy elements may include at least one element selected from the group consisting of Mg, Ti, Al, Zn, Ca, Sn, Pb, Fe, Mn, Te, Nb, P, Co, Sb, Bi, Ag, Ta, W, and Mo. Here, the total amount of additive elements and impurity elements (excluding O, H, S, and N) other than the alloy elements constituting the copper alloy particles 50 of the copper alloy powder for metal AM may be 0.07 mass% or less, 0.06 mass% or less, or 0.05 mass% or less, preferably 0.04 mass% or less, more preferably 0.03 mass% or less, even more preferably 0.02 mass% or less, and even more preferably 0.01 mass% or less. In addition, the upper limit of the content of each of the additive elements and impurity elements (excluding O, H, S, and N) other than the alloy elements constituting the copper alloy particles 50 of the copper alloy powder for metal AM is preferably 30 massppm or less, more preferably 20 massppm or less, and even more preferably 15 massppm or less.

[0049] The copper alloy constituting the copper alloy particles 50 of the copper alloy powder for metal AM of this embodiment may contain Cr in the range of 0.01 mass% to 10 mass% and the balance may be composed of copper and impurities. The copper alloy constituting the copper alloy particles 50 of the copper alloy powder for metal AM of this embodiment may contain Cr in the range of 0.01 mass% to 10 mass% and the balance may be composed of copper, the above-mentioned additive elements, and impurity elements.

[0050] In the copper alloy powder for metal AM of this embodiment, it is preferable that the volume-based 50% cumulative particle diameter D50 measured by a laser diffraction / scattering method is in the range of 5 μm or more and 120 μm or less, the 10% cumulative particle diameter D10 is in the range of 1 μm or more and 80 μm or less, and the 90% cumulative particle diameter D90 is in the range of 10 μm or more and 150 μm or less.

[0051] The lower limit of the 50% cumulative particle size D50 is more preferably 10 μm or more, and even more preferably 15 μm or more.The upper limit of the 50% cumulative particle size D50 is more preferably 100 μm or less, and even more preferably 90 μm or less. The lower limit of the 10% cumulative particle size D10 is more preferably 5 μm or more, and even more preferably 10 μm or more. The upper limit of the 10% cumulative particle size D10 is more preferably 70 μm or less, and even more preferably 60 μm or less. Furthermore, the lower limit of the 90% cumulative particle size D90 is more preferably 20 μm or more, and even more preferably 30 μm or more.The upper limit of the 90% cumulative particle size D90 is more preferably 140 μm or less, and even more preferably 120 μm or less.

[0052] An example of a method for producing copper alloy powder for metal AM according to the present embodiment will be described with reference to the flow diagram of Fig. 7. Note that, in this embodiment, copper alloy powder suitable for the laser PBF method is produced. The manufacturing method of copper alloy powder for metal AM according to this embodiment includes a melting and casting step S01 for obtaining a copper alloy ingot, a copper alloy raw material preparation step S02 for processing the obtained copper alloy ingot into a wire rod to obtain a copper alloy raw material, and a powder processing step S03 for processing the copper alloy raw material into powder.

[0053] (Melting and casting process S01) First, a copper alloy ingot having a predetermined composition is produced. The melting and casting process S01 includes a melting step, an alloy element adding step, and a continuous casting step. In this embodiment, a copper alloy ingot 1 is produced using a continuous casting apparatus 10 shown in FIG. This continuous casting apparatus 10 includes a melting furnace 11, a tundish 12 arranged downstream of the melting furnace 11, a connecting trough 13 connecting the melting furnace 11 and the tundish 12, an addition section 14 for adding alloy elements in the tundish 12, a continuous casting mold 15 arranged downstream of the tundish 12, and a pouring nozzle 16 for pouring molten copper alloy from the tundish 12 into the continuous casting mold 15.

[0054] In the melting furnace 11 of the molten copper supply section, the copper raw material is melted in a non-oxidizing atmosphere (an inert gas atmosphere or a reducing atmosphere) to obtain the molten copper 3 (melting step). Here, the copper raw material melted in the melting furnace 11 is high-purity copper with a purity of 99.99 mass% or more (e.g., high-purity electrolytic copper or oxygen-free copper). The copper raw material to be melted is high-purity copper of 4N grade (99.99 mass%) or more, more preferably high-purity copper of 5N grade (99.999 mass%) or more, and even more preferably high-purity copper of 6N (99.9999 mass%) or more. The obtained molten copper 3 is preferably oxygen-free molten copper.

[0055] In the connecting trough 13, the obtained molten copper 3 is supplied to the tundish 12 while maintaining a non-oxidizing atmosphere (an inert gas atmosphere or a reducing atmosphere). The connecting trough 13 is disposed between the melting furnace 11 and the tundish 12, and the molten copper 3 passes through the inside of the connecting trough 13 in a non-oxidizing atmosphere. In addition, in the tundish 12, the molten copper 3 is held in a non-oxidizing atmosphere (an inert gas atmosphere or a reducing atmosphere). In addition, since the melting furnace 11, the connecting trough 13, and the tundish 12 are in a non-oxidizing atmosphere (an inert gas atmosphere or a reducing atmosphere), the gas components (O, H) in the molten copper 3 are reduced.

[0056] Then, in the tundish 12, alloy elements are appropriately added to the molten copper 3 using the adding section 14 (alloy element adding step). Also, additive elements may be appropriately added here. By adding alloying elements to the molten copper 3 in which the gas components (O, H) have been sufficiently reduced, the yield of the alloying elements added is good, so that the amount of the alloying elements used can be reduced, and the manufacturing cost of the copper alloy can be reduced. Furthermore, by adding alloying elements to the molten copper 3 flowing inside the tundish 12, the alloying elements can be uniformly dissolved, and a molten copper alloy having stable component values ​​can be continuously produced.

[0057] The obtained molten copper alloy is poured into a continuous casting mold 15 through a pouring nozzle 16 to continuously produce a copper alloy ingot 1 (continuous casting process). In this embodiment, a copper alloy ingot having a circular cross section is produced.

[0058] In this embodiment, the obtained copper alloy ingot 1 has an O concentration of 10 massppm or less and an H concentration of 5 massppm or less. In the obtained copper alloy ingot 1, the S concentration is preferably 15 massppm or less. Furthermore, in the obtained copper alloy ingot 1, the total content of additive elements and impurity elements other than Cu and alloy elements is preferably 0.04 mass% or less.

[0059] (Copper alloy raw material preparation process S02) Next, the copper alloy ingot obtained in the melting and casting step S01 is processed into a wire rod to produce a copper alloy raw material. The copper alloy raw material preparation step S02 includes an extrusion step, a drawing step, and a cutting step. In this copper alloy raw material preparation step S02, first, a copper alloy ingot having a circular cross section is heated and processed by hot extrusion into a rod having a predetermined diameter (extrusion step). In this embodiment, the heating temperature during the hot extrusion process is preferably set within a range of 700°C or more and 1000°C or less.

[0060] Next, the obtained rod is drawn to produce a wire having a predetermined diameter (drawing step). The temperature for the drawing is not particularly limited, but is preferably within the range of -200°C to 200°C, which corresponds to cold or warm rolling, and particularly preferably at room temperature.

[0061] The obtained wire is then cut to a predetermined length to provide a copper alloy raw material (cutting step). Here, it is preferable that the O concentration in the obtained copper alloy raw material is 10 massppm or less, and the H concentration is 5 massppm or less. In addition, it is preferable that the S concentration in the obtained copper alloy raw material is 15 massppm or less. Furthermore, the total content of additive elements and impurity elements (excluding O, H, and S) other than Cu and alloy elements in the obtained copper alloy raw material is preferably 0.04 mass% or less.

[0062] (Powder processing process S03) Next, the copper alloy raw material obtained in the copper alloy raw material preparation step S02 is subjected to an atomization process to produce copper alloy powder for metal AM. This powder processing step S03 includes a melting step, an atomizing step, and a classification step. In the melting step, the copper alloy raw material is heated and melted to obtain a molten alloy. In this embodiment, the melting atmosphere is preferably a non-oxidizing atmosphere. In the atomization process, powder is obtained by, for example, gas atomization. That is, the molten alloy obtained in the melting process is sprayed with high-pressure gas to rapidly cool the droplets of the molten alloy, thereby producing powder having a spherical or similar shape. Inert gases such as argon and nitrogen can be used as the gas used in the gas atomization process. In the classification step, the obtained powder is classified to obtain a copper alloy powder having a predetermined particle size distribution. The melting temperature of the copper alloy raw material in the gas atomization process (the temperature during the gas atomization process) is preferably not lower than the melting point of copper and not higher than 1500°C. The melting temperature during the gas atomization process may be not lower than 1085°C and not higher than 1500°C.

[0063] Here, in this embodiment, as described above, the atomization process is performed using a molten alloy derived from a copper alloy raw material in which the content of impurity elements (excluding O, H, S, and N) has been sufficiently reduced, so that alloy elements such as Cr are prevented from reacting with and being consumed by the impurity elements (excluding O, H, S, and N), and it becomes possible to generate a Cr-containing compound. Furthermore, in this embodiment, the atomization process is performed using a molten alloy derived from a copper alloy raw material in which the content of impurities (components including impurity elements and O, H, S, and N) has been sufficiently reduced. This prevents alloy elements such as Cr from reacting with and being consumed by the impurities (components including impurity elements and O, H, S, and N), making it possible to generate a Cr-containing compound.

[0064] The copper alloy powder for metal AM according to the present embodiment is produced by the above-mentioned steps. In the copper alloy powder for metal AM according to the present embodiment, the O concentration is preferably 1000 massppm or less, the H concentration is preferably 5 massppm or less, and the S concentration is preferably 10 massppm or less. Specifically, the O concentration may be about 2700 massppm or less, preferably 1000 massppm or less, and more preferably 900 massppm or less. The lower limit of the O concentration is not particularly limited, but may be a value that does not include 0 (or a value that exceeds 0). If the O concentration is high, foreign matter such as oxygen or oxides may remain in the molded product, which may deteriorate various properties of the molded product. The H concentration may be 90 massppm or less, may be 60 massppm or less, and is preferably 5 massppm or less. The lower limit of the H concentration is not particularly limited, but may be a value that does not include 0 (or a value that exceeds 0). The S concentration may be 90 massppm or less, may be 60 massppm or less, and is preferably 30 massppm or less. Furthermore, the S concentration in the copper alloy powder for metal AM is more preferably 10 massppm or less. In addition, the lower limit of the S concentration is not particularly limited, but may be a value that does not include 0 (or a value that exceeds 0). In addition, in a process carried out under a finite pressure, such as atomization, atmospheric components contained in the atmosphere or during the process may cause atmospheric components to be contained in the powder. For example, nitrogen derived from atmospheric components may be contained in the powder. In the copper alloy powder for metal AM, the nitrogen concentration (N concentration) is preferably 30 massppm, more preferably 20 massppm, and even more preferably 10 massppm or less. In the copper alloy powder for metal AM of this embodiment, the nitrogen concentration (N concentration) is preferably 30 massppm, more preferably 20 massppm, and may be 10 massppm or less, and even more preferably 5 massppm or less. In addition, the lower limit of the N concentration is not particularly limited, but may be a value that does not include 0 (or a value that exceeds 0).

[0065] In addition, copper alloy powder for metal AM may contain additive elements and impurity elements other than alloy elements as long as they do not affect the characteristics. Here, the total amount of additive elements and impurity elements (excluding O, H, S, and N) may be 0.07 mass% or less, may be 0.06 mass% or less, may be 0.05 mass% or less, is preferably 0.04 mass% or less, is more preferably 0.03 mass% or less, is further preferably 0.02 mass% or less, and is further preferably 0.01 mass% or less. In addition, the upper limit of each of the contents of additive elements and impurity elements (excluding O, H, S, and N) is preferably 30 massppm or less, more preferably 20 massppm or less, and even more preferably 15 massppm or less.

[0066] Next, the method for producing a layered object according to this embodiment will be described with reference to the flow chart of FIG. The manufacturing method of an additive manufacturing object in this embodiment includes a preparation step S101 of preparing the above-mentioned copper alloy powder for metal AM, a first step S121 of forming a powder bed containing the copper alloy powder for metal AM, and a second step S122 of solidifying the copper alloy powder for metal AM at a predetermined position in the powder bed to form a modeling bed, thereby sequentially repeating these steps to produce an additive manufacturing object. Through these steps, an additive manufacturing process is performed to produce an additive manufacturing product having a predetermined shape. Since the additive manufacturing product uses the copper alloy powder for metal AM according to the present embodiment, the additive manufacturing product has few structural defects such as voids and has excellent mechanical properties.

[0067] Particle 50 constituting the copper alloy powder for metal AM of this embodiment, configured as described above, is made of a copper alloy containing Cr, and a Cr compound layer 52 having a Cr-containing compound is formed on the surface of the particle body 51. This means that laser absorption is efficient on the particle surface, and the microstructure of the object produced by metal AM is highly reproducible, making it possible to consistently produce high-quality additively manufactured objects with few structural defects such as voids.

[0068] In the particle 50 constituting the copper alloy powder for metal AM of this embodiment, when the Cr compound layer 52 contains an oxide of an element that constitutes the copper alloy of the particle body 51, laser absorption on the particle surface is more efficient, making it possible to stably produce high-quality additively molded objects with high reproducibility of the microstructure of the object produced by metal AM and with few structural defects such as voids.

[0069] Furthermore, in the case of particle 50 constituting the copper alloy powder for metal AM of this embodiment, when a cross-sectional observation of the particle body 51 reveals that Cr-containing compounds are distributed at the grain boundaries, it is possible to produce an additive manufacturing object with excellent electrical conductivity, thermal conductivity, and strength.

[0070] Here, in the particle 50 constituting the copper alloy powder for metal AM of this embodiment, when the copper alloy constituting the particle body 51 contains Zr and a Zr-containing compound is distributed on the surface of the particle body 51, laser absorption on the particle surface becomes even more efficient, and the microstructure of the object produced by metal AM is highly reproducible, making it possible to stably produce high-quality additively manufactured objects with few structural defects such as voids.

[0071] Furthermore, in particle 50 constituting the copper alloy powder for metal AM of this embodiment, if the copper alloy constituting particle body 51 contains Zr, and Zr-containing compounds are distributed at the crystal grain boundaries when the particle body 51 is observed in cross section, it is possible to produce an additive manufacturing object with excellent electrical conductivity, thermal conductivity, and strength.

[0072] Furthermore, in the copper alloy powder for metal AM of this embodiment, when the volume-based 50% cumulative particle diameter D50 measured by a laser diffraction / scattering method is within the range of 5 μm or more and 120 μm or less, it has a particle size distribution suitable for metal AM, making it possible to stably manufacture additive manufacturing objects.

[0073] Furthermore, in the copper alloy powder for metal AM of this embodiment, when the volume-based 10% cumulative particle diameter D10 measured by a laser diffraction / scattering method is within the range of 1 μm or more and 80 μm or less, it has a particle size distribution suitable for metal AM, and it becomes possible to stably manufacture additive manufacturing objects.

[0074] Furthermore, in the copper alloy powder for metal AM of this embodiment, when the volume-based 90% cumulative particle diameter D90 measured by a laser diffraction / scattering method is within the range of 10 μm or more and 150 μm or less, it has a particle size distribution suitable for metal AM, and it becomes possible to stably manufacture additive manufacturing objects.

[0075] In the manufacturing method for additive manufacturing of this embodiment, the copper alloy powder for metal AM of this embodiment is used, so it is possible to consistently produce high-quality additive manufacturing objects with high reproducibility of the microstructure of the object produced by metal AM and with few structural defects such as voids.

[0076] The copper alloy powder for metal AM and the method for manufacturing an additive manufacturing object according to the embodiment of the present invention have been described above. However, the present invention is not limited thereto and can be modified as appropriate without departing from the technical concept of the invention. For example, in the above-described embodiment, the copper alloy powder for metal AM is produced by gas atomization, but this is not limited to this, and the copper alloy powder for metal AM may be produced by water atomization, centrifugal atomization, plasma atomization, or the like.

[0077] In addition, the copper alloy powder for metal AM obtained as described above may be appropriately heat-treated in a controlled atmosphere to stabilize the structure. Furthermore, in this embodiment, the copper alloy powder for metal AM suitable for the PBF method using a laser has been described as being produced, but this is not limited to this, and the copper alloy powder for metal AM may be applied to other metal AM. In addition, in the present embodiment, the continuous casting apparatus shown in FIG. 8 is used to produce a copper alloy ingot, but the present invention is not limited to this, and other casting apparatuses may be used.

[0078] For example, a continuous casting apparatus 101 shown in Fig. 10 may be used. This continuous casting apparatus 101 includes an oxygen-free copper supplying means (molten copper supplying section) 102 arranged at the most upstream portion, a heating furnace 103 arranged downstream thereof, a tundish 104 arranged downstream of the heating furnace 103 and supplied with molten copper, molten metal supplying passages 105a, 105b, and 105c connecting the oxygen-free supplying means 102 to the heating furnace 103, a trough 106 connecting the heating furnace 103 and the tundish 104, addition means (adding sections) 107 and 108 for adding alloy elements in a non-oxidizing atmosphere, and a continuous casting mold 42. The oxygen-free copper supplying means 102, the heating furnace 103, the tundish 104, the molten metal supplying passages 105a, 105b, and 105c, and the trough 106 each have a non-oxidizing atmosphere inside.

[0079] The oxygen-free copper supply means 102 is composed of a melting furnace 121 for melting the copper raw material, a holding furnace 122 for temporarily holding the molten copper obtained by melting in the melting furnace 121, a degassing treatment device 124 for removing oxygen and hydrogen from the molten copper, and molten metal supply paths 105a, 105b, and 105c connecting these.

[0080] The degassing treatment device 124 has a gas bubbling device as stirring means for stirring the molten copper therein, and removes oxygen and hydrogen from the molten copper by bubbling with an inert gas, for example. The molten metal supply passages 105a, 105b, and 105c have a non-oxidizing atmosphere therein to prevent the molten copper and the oxygen-free copper molten metal from being oxidized. The non-oxidizing atmosphere is formed by blowing an inert gas such as a mixture of nitrogen and carbon monoxide or argon into the molten metal supply passages.

[0081] As adding means for adding alloy elements, a first adding means 107 disposed in the heating furnace 103 and a second adding means 108 disposed in the tundish 104 are provided. When alloying elements are continuously or intermittently charged from first adding means 107 provided in heating furnace 103, the alloying elements are added to the oxygen-free copper molten metal stored in heating furnace 103. Here, the oxygen-free copper molten metal stored in the storage section is heated by a high-frequency induction coil, which promotes the melting of the added alloying elements. Furthermore, when alloying elements are continuously or intermittently charged from the second adding means 108 provided in the tundish 104, the alloying elements are added to the molten oxygen-free copper flowing in the tundish 104. Here, the molten oxygen-free copper flowing in the tundish 104 is heated in the heating furnace 103 and has a high temperature, and also flows within the tundish 104, which promotes the dissolution of the added alloying elements. EXAMPLES

[0082] The results of experiments carried out to confirm the effects of the present invention will be described below.

[0083] (Example of the present invention) First, by the manufacturing method described in the embodiment, a copper raw material consisting of 4N grade high purity copper was used to produce ingots of C18000 and C18150 having the compositions shown in Table 1 (the impurities shown in Table 1 exclude O, H, and S from the impurities). Next, using the produced C18000 and C18150 ingots as raw materials, C18000 powder for metal AM and C18150 powder for metal AM with the compositions shown in Table 2 were produced by gas atomization using argon gas, and classified to a particle size suitable for the powder bed of laser PBF (the impurities shown in Table 2 exclude O, H, S, and N from the impurities.) The melting temperature during gas atomization was 1300°C.

[0084] For the C18000 powder for metal AM of the present invention, particle size distribution measurement was performed using a Microtrac MT3300EXII. The particle size distribution was as follows: 10% cumulative particle size by volume was 15 μm, 50% cumulative particle size was 27 μm, and 90% cumulative particle size was 45 μm. The particle size distribution of the C18150 powder for metal AM of the present invention was measured using a Microtrac MT3300EXII. The particle size distribution was as follows: 10% cumulative particle size by volume was 19 μm, 50% cumulative particle size was 30 μm, and 90% cumulative particle size was 49 μm. Then, using the C18000 powder for metal AM of the present invention, a commercially available laser PBF device was used to perform laser beam splitting at an energy density of 13 J / mm 2 A small piece of an additive manufacturing object was produced under the conditions of 1. Using the C18150 powder for metal AM of the present invention, a commercially available laser PBF device was used with an energy density of 5 J / mm 2 A small piece of the additive manufacturing object was produced under the above conditions.

[0085] (Surface structure of copper alloy powder for metal AM) The microstructure of the particle surface of each of the C18000 powder for metal AM and the C18150 powder for metal AM of the present invention was evaluated using Auger electron spectroscopy. The results of the Auger electron spectroscopy analysis of the surfaces of the particles constituting the copper alloy powder for metal AM are shown in Figures 2A to 2E, 3A to 3C, and 4A and 4B.

[0086] (Cross-sectional structure of copper alloy powder for metal AM) The microstructure of the particle cross section of the C18000 powder for metal AM and the C18150 powder for metal AM of the present invention was evaluated using Auger electron spectroscopy and scanning electron microscopy. The analysis results of the cross sections of the particles constituting the copper alloy powder for metal AM are shown in Figures 5A and 5B and 6A to 6C.

[0087] (Composition of copper alloy powder for ingot and metal AM) The O concentration in the ingots shown in Table 1 and the copper alloy powders for metal AM of the present invention shown in Table 2 was determined by inert gas fusion-infrared absorption method, the H concentration by inert gas fusion-thermal conductivity method, and the S concentration by combustion-infrared absorption method. In addition, the concentrations of components other than these substances, except for copper, were determined by a combination of X-ray fluorescence analysis, glow discharge mass spectrometry, and inductively coupled plasma mass spectrometry.

[0088] (model density) The density of the layered object was evaluated from the cross section of the layered object and the area occupied by voids observed in the cross section of the layered object. In this specification, this density is defined as the density of the object. The density of the molded object was evaluated by first defining the cross-sectional area to be measured on the cross section of the molded object (this is called the evaluation cross-sectional area; 3.4 mm square), identifying the void locations within this measurement cross-sectional area, and then calculating the area occupied by the voids in the evaluation cross-sectional area. The density of the molded object was defined as (evaluated cross-sectional area - void occupied area) / evaluated cross-sectional area. The evaluation results of the density of the molded object are shown in Table 2.

[0089] (Evaluation of mechanical properties and electrical conductivity of the object) The produced layered object was subjected to a heat treatment as described below, and the Vickers hardness and electrical conductivity of the layered object after the heat treatment were measured. As a mechanical property of the fabricated additive objects, the Vickers hardness (HV unit) was measured at room temperature in accordance with JIS Z 2244: 2009. The Vickers hardness measurement load was 10 kgf. The electrical conductivity (%IACS unit) of the fabricated additive objects was also measured at room temperature using an eddy current electrical conductivity meter. The properties of these objects are shown in Table 2.

[0090] (Presence or absence of CrSi-based compounds and NiSi-based compounds on the surface of copper alloy particles) The presence or absence of CrSi-based compounds and NiSi-based compounds on the surfaces of the copper alloy particles constituting the copper alloy powder for metal AM of the present invention was confirmed by high-angle annular dark-field scanning transmission microscopy. The analysis results are shown in Figures 11 and 12.

[0091] (Presence or absence of Cr-containing compounds and Zr-containing compounds on the surface of copper alloy particles) The presence or absence of Cr-containing compounds and Zr-containing compounds on the surfaces of the copper alloy particles constituting the copper alloy powder for metal AM of the present invention was confirmed by high-angle annular dark-field scanning transmission microscopy and transmission electron microscopy. The analysis results are shown in Figures 13 to 15.

[0092] [Table 1]

[0093] [Table 2]

[0094] 2A to 2E and 3A to 3C are the results of Auger electron spectroscopy after ion etching of the particle surface of the copper alloy powder for metal AM of the present invention (FIGS. 2A to 2E are C18000 powder, and FIG. 3A to 3C are C18150 powder). The etching rate of each element alone or each compound generated by each element on the particle surface of the copper alloy powder of the present invention in the experimental system of this Auger electron spectroscopy analysis is not clear, but since the etching rate of SiO2 in the experimental system of this Auger electron spectroscopy analysis is 1.08 nm / min, it is considered that the structure after 15 minutes of ion etching is approximately 15 nm thick. As shown in FIG. 2A and FIG. 3A, many island-shaped fine structures appeared on the particle surface after ion etching.

[0095] Furthermore, comparison of Figs. 2A, 2B and 2E, and Figs. 3A and 3B confirmed that the island-like microstructure originated from Cr-based precipitates.

[0096] 16A to 16F show the results of Auger electron spectroscopy analysis of the particle surface of the copper alloy particles constituting the copper alloy powder (C18000) for metal AM of the present invention, and show Cr mapping images before ion etching the particle surface, and after ion etching for 5 minutes, 15 minutes, 30 minutes, and 50 minutes. First, as shown in Fig. 16A and Fig. 16B, it can be seen that Cr-based precipitates are distributed in an island shape on the copper grain boundaries and on the copper grains (copper grain surfaces) on the outermost particle surface before ion etching. The distribution of Cr confirmed in Fig. 16A and Fig. 16B is thought to be derived from Cr-containing compounds. As shown in Figures 16B to 16F, the structure of the island-like microstructure on the particle surface changes with the ion etching time. As shown in Figure 16F, the distribution of Cr-based precipitates is confirmed even after 50 minutes of ion etching, but compared with Figures 16C and 16D, it is confirmed that the distribution points of Cr tend to decrease. In addition, from the etching rate of SiO2 in the experimental system of this Auger electron spectroscopy analysis and the state of the structural change of the particle surface with the etching time in Figures 16B to 16F, it was considered that the thickness of the Cr compound layer 52 containing Cr-containing compounds in the copper alloy powder (C18000) for metal AM of the present invention is in the range of approximately 1 nm to 100 nm.

[0097] On the other hand, Figure 3C shows the results of Auger electron spectroscopy of the surface of a single copper crystal particle after ion etching the outermost surface of the copper alloy powder for metal AM (C18150) of the present invention for 30 minutes. From the above SiO2 etching rate, it is considered that the structure after ion etching for 30 minutes is approximately 30 nm thick. As shown in Figure 3C, after ion etching for 30 minutes, it was confirmed that Cr and Zr were present in addition to Cu on the copper crystal particles on the particle surface of the copper alloy powder for metal AM of the present invention, while the island-like structure became difficult to see. Therefore, the thickness of the surface layer containing Cr-based precipitates present on the particle surface, i.e., the Cr compound layer 52 containing Cr-containing compounds in the copper alloy powder for metal AM of the present invention (C18150), was considered to be in the range of approximately 1 nm to 100 nm.

[0098] Considering the results of Figures 16A to 16F and Figures 3A to 3C as a whole, it was considered that the thickness of the surface layer containing Cr-based precipitates present on the particle surfaces of the copper alloy powder for metal AM of the present invention, i.e., the Cr compound layer 52 containing Cr-containing compounds, was in the range of approximately 1 nm to 100 nm.

[0099] 4A and 4B are oxygen intensity depth profiles by Auger electron spectroscopy of the particle surface of the copper alloy powder for metal AM of the present invention (FIG. 4A is C18000 powder, and FIG. 4B is C18150 powder). It was confirmed that the concentration of oxygen contained in the copper alloy powder for metal AM of the present invention decreases from the outermost surface of the copper alloy particle toward the inside of the copper alloy particle. In essence, since the copper alloy powder for metal AM of the present invention contains oxygen as a copper alloy, a certain amount of oxygen exists in the particle body, and this is considered to constitute the background concentration of the oxygen concentration in the particle body. On the other hand, the gradient of the oxygen concentration observed on the particle surface is mainly generated in the powdering process, and further, from the results of FIG. 4A and FIG. 4B, it is considered to exist in the range of about 1 nm to 100 nm, and it is considered that the gradient of the oxygen concentration may occur on the order of the thickness of the surface layer containing the above-mentioned Cr-based precipitates.

[0100] From the results shown in Figures 2A to 2E, 3A to 3C, and 4A and 4B, it was confirmed that a Cr compound layer 52 containing Cr-containing compounds derived from Cr-based precipitates is formed on the particle surfaces of the copper alloy powder for metal AM of the present invention at the copper grain boundaries and on the copper grains (surfaces of the copper grains), and that this Cr compound layer 52 is a layer containing oxygen. In other words, the presence of such an oxygen-containing layer in the copper alloy powder for metal AM of the present invention is considered to provide an effect of suppressing surface deterioration of the copper alloy powder. 2A to 2E, 3A to 3C, 4A, and 4B, the copper alloy powder for metal AM of the present invention is mainly composed of Cu, which is the parent phase, and therefore it is presumed that such oxygen is mainly derived from copper oxide, and further presumed to be present as a constituent element of oxides of alloying elements and other impurity elements. That is, it is presumed that the Cr compound layer on the surface of the copper alloy powder for metal AM of the present invention forms a composite layer composed of Cu, copper oxide, oxides of alloying elements containing Cr, and the like, while encapsulating compounds containing Cr.

[0101] The density of precipitates derived from Cr-containing compounds in the Cr compound layer 52 of the particles of the copper alloy powders for metal AM (C18000 powder and C18150 powder) of the present invention was measured using an image of the outermost surface of the Cr compound layer 52 analyzed by Auger electron spectroscopy using a scanning Auger electron spectrometer PHI700xi manufactured by ULVAC-PHI, Inc. 2 The area occupancy of Cr-containing compounds (Cr-based precipitates) was calculated from the size and number of precipitates of Cr-containing compounds per unit area. On the outermost surface of the Cr compound layer 52 of the copper alloy powder for metal AM (C18000 powder), there were areas where the precipitate density was 17% by area and areas where the precipitate density was 21% by area (see Figures 2A and 2B), and on the outermost surface of the Cr compound layer 52 of the copper alloy powder for metal AM (C18000 powder), there were areas where the precipitate density was 16% by area and areas where the precipitate density was 28% by area.

[0102] In addition, the copper grain boundaries of the images of the Cr compound layer 52 of the particles of the copper alloy powders for metal AM (C18000 powder and C18150 powder) of the present invention analyzed by Auger electron spectroscopy using a scanning Auger electron spectrometer PHI700xi manufactured by ULVAC-PHI, Inc. were observed, and the linear density per 1 μm of grain boundary length was calculated from the proportion of precipitates derived from Cr-containing compounds per 1 μm of grain boundary length. In the Cr compound layer 52 of the copper alloy powder for metal AM (C18000 powder), the linear density of the precipitates at the copper grain boundaries was observed to be 31% and 60% at some places. In the Cr compound layer 52 of the copper alloy powder for metal AM (C18150 powder), the linear density of the precipitates at the copper grain boundaries was observed to be 59% and 74% at some places.

[0103] In addition, as shown in Fig. 5A, Fig. 5B and Fig. 6A to Fig. 6C, in the cross-sectional observation of the copper alloy particles, the precipitation of Cr-containing compounds was confirmed in the copper crystal grain boundaries in common in the particles constituting the copper alloy powder for metal AM of the present invention (Fig. 4A and Fig. 5B are C18000 powder, Fig. 6A to Fig. 6C are C18150 powder). In addition, compared with the particle surface, the precipitation of Cr-containing compounds was not observed in the inside of the particles as frequently as that observed in the grain boundaries. In other words, it is shown that Cr-containing compounds are observed frequently on the particle surface. This was predicted to be either that there were almost no Cr-based precipitates in the copper crystal grains, or that the Cr-based precipitates in the inside of the copper crystal grains were very small (or the amount was small) and difficult to observe. On the other hand, from the comparison of Fig. 2B to Fig. 2E with Fig. 5A to Fig. 5B, that is, from the comparison of the particle surface and the particle cross section, it was thought that the proportion of precipitates occupying a certain surface of the particle would be greater on the outermost surface (or surface layer) of the particle than in the inside of the particle.

[0104] 5A and 5B, the presence of either or both of CrSi-based precipitates and NiSi-based precipitates was confirmed at the grain boundaries inside the particles of the copper alloy powder for metal AM. This result shows that either or both of CrSi-based precipitates and NiSi-based precipitates are present at the grain boundaries inside the Cr compound layer on the particle surface of the particles of the copper alloy powder for metal AM.

[0105] On the other hand, as representatively shown in Figures 6A and 6B, the presence of Cr-based precipitates was confirmed at the grain boundaries inside the particles of the copper alloy powder for metal AM. This result indicates that Cr-based precipitates exist at the grain boundaries inside the Cr compound layer on the particle surface of the particles of the copper alloy powder for metal AM. These results indicate that Cr-based precipitates exist at the grain boundaries from the surface to the interior, below the Cr compound layer on the particle surface of the particles of copper alloy powder for metal AM.

[0106] As shown in Figure 11, the results of analysis of the copper alloy particle surfaces of the copper alloy powder for metal AM of the present invention using a high-angle annular dark-field scanning transmission microscope confirmed that the CrSi-based compounds formed on the surfaces of the copper alloy particles of the copper alloy powder for metal AM of the present invention contain Cr3Si. Also, as shown in Figure 12, analysis of the electron diffraction pattern confirmed that in the case of Figure 10, Cr3Si is formed in lattice matching with Cu crystals.

[0107] As shown in Figures 13 and 14, the results of analysis of the surfaces of the copper alloy particles of the copper alloy powder for metal AM of the present invention using a transmission electron microscope confirmed that the Cr-based compounds formed on the surfaces of the copper alloy particles of the copper alloy powder for metal AM of the present invention contain Cr and Cr2Zr(Hexagonal)[-21-4].

[0108] As shown in Figure 15, the results of a transmission electron microscope analysis of the surfaces of the copper alloy particles of the copper alloy powder for metal AM of the present invention confirmed that the Zr-based compounds formed on the surfaces of the copper alloy particles of the copper alloy powder for metal AM of the present invention include Cu8Zr3 (Orthorhombic)[21-4].

[0109] As shown in Table 2, when a mold was produced using the copper alloy powder for metal AM of the C18000 composition of the present invention in which a Cr-containing compound was formed on the particle surface, the density of the molded object was 99.3%. This result suggests that the copper alloy powder for metal AM of the present invention promotes sufficient laser absorption, resulting in a high density molded object. Furthermore, a heat-treated molded body was produced by subjecting the C18000 composition laminated object to a first heat treatment at 950°C for 15 minutes and a second heat treatment at 420°C for 2.2 hours. This heat-treated molded body showed a Vickers hardness of 194HV and a conductivity of 40%IACS at room temperature (see Table 2). As shown in Table 2, when a mold was manufactured using the copper alloy powder for metal AM of the C18150 composition of the present invention in which a Cr-containing compound was formed on the particle surface, the density of the molded object was 99.6%. From this result, it is believed that the copper alloy powder for metal AM of the present invention promotes sufficient laser absorption, resulting in a high density molded object. Furthermore, a heat-treated molded body was produced by subjecting the C18150 composition laminated object to a first heat treatment at 980°C for 15 minutes and a second heat treatment at 450°C for 1.0 hour. This heat-treated molded body showed a Vickers hardness of 130HV and a conductivity of 90%IACS at room temperature (Table 2). These results demonstrate that the copper alloy powder for metal AM of the present invention can be used to produce additively molded objects with few voids, which is important for practical use, and that the powder has sufficient mechanical properties and electrical conductivity for practical use, making it possible to realize practical copper alloy additively molded objects. [Explanation of symbols]

[0110] 50 Copper alloy particles constituting copper alloy powder for metal AM 51 Particle body 52 Cr compound layer

Claims

1. A copper alloy powder for metal AM used in metal AM, The copper alloy contains 0.1% by mass or more and 1.5% by mass or less of Cr as an alloy element, In the case where one or more alloy elements selected from Zr, Si, and Ni are contained as alloy elements other than Cr, the Zr content is 0.2 mass% or less, the Si content is 0.8 mass% or less, and the Ni content is 3.0 mass% or less. The total amount of additive elements and impurity elements (excluding O, H, S, and N) other than the alloy elements is 0.07 mass% or less, A copper alloy powder for metal AM, characterized in that a Cr compound layer containing a Cr-containing compound is formed on the surface of copper alloy particles constituting the copper alloy powder.

2. 2. The copper alloy powder for metal AM according to claim 1, characterized in that the Cr compound layer on the surface of the copper alloy particles contains oxygen.

3. 2. The copper alloy powder for metal AM according to claim 1, characterized in that, in cross-sectional observation of the copper alloy particles constituting the copper alloy powder, Cr-containing compounds are distributed at crystal grain boundaries throughout the copper alloy particles.

4. 2. The copper alloy powder for metal AM according to claim 1, characterized in that the volume-based 50% cumulative particle diameter D50 measured by a laser diffraction / scattering method is in the range of 5 μm or more and 120 μm or less.

5. 2. The copper alloy powder for metal AM according to claim 1, characterized in that the volume-based 10% cumulative particle diameter D10 measured by a laser diffraction / scattering method is in the range of 1 μm or more and 80 μm or less.

6. The copper alloy powder for metal AM according to claim 1, characterized in that the volume-based 90% cumulative particle diameter D90 measured by a laser diffraction / scattering method is in the range of 10 μm or more and 150 μm or less.

7. A preparation step of preparing the copper alloy powder for metal AM according to any one of claims 1 to 6; a molding process for producing an additive object by sequentially repeating a first process for forming a powder bed containing the copper alloy powder for metal AM and a second process for solidifying the copper alloy powder for metal AM at a predetermined position in the powder bed to form a molding bed; A method for manufacturing a layered object, comprising:

8. The method for manufacturing a layered object according to claim 7, further comprising a heat treatment step of performing a heat treatment at a temperature range of 300° C. or higher and lower than the melting point of pure copper after the shaping step.

Citation Information

Patent Citations

  • Method for improving CuCrZr material performances

    CN111676386A

  • Manufacturing method of alloy structure

    JP2016023366A

  • Copper alloy powder, manufacturing method of laminate molded article and laminate molded article

    JP2016211062A

  • Copper alloy powder, heat treatment method for multilayer shaped structure, method for producing copper alloy shaped structure, and copper alloy shaped structure

    JP2019070169A

  • Copper powder having excellent laser light absorbency

    JP2020186429A